Using Executive Function to Enhance Reasoning Thinking of Preschool Children: What Teachers Shouldn’t Overlook - Muangthong, Wunwisa; Kaewurai, Wareerat; Onthanee, Angkana; Juntakun, Jakkrit (Ratchaphruek Journal, 2020)
Preschool children can be considered a golden opportunity for learning. Because children of this age, the brain is growing rapidly If the child is cultivated, promoted, developed and motivated in the correct way Suitable according to age and according to that potential Will help develop brain cells causing affecting the intelligence in children. This academic article aims to present knowledge about promoting reasoning thinking. Which is one skill that should be promoted in preschool children. It is one of the characteristics of thinking that is necessary in daily life of children, including high level of learning. And the Executive Function in order to help develop the reasoning thinking of children in accordance with the guidelines that correspond to the potential of human brain development. Early childhood teachers, including those involved. It should be combined with the use of thinking skills for successful life to promote rational thinking with preschool children to be more efficient and effective.